Synthesis and characterization of monoacylglycerols through glycerolysis of ethyl esters derived from linseed oil by green processes. Issue 4 (13th January 2020) - Hobuss, Cristiane B.; da Silva, Felipe A.; dos Santos, Marco A. Z.; de Pereira, Claudio M. P.; Schulz, Gracélie A. S.; Bianchini, Daniela
Abstract : The synthesis of monoacylglycerol (MAG) through the glycerolysis of ethyl ester mixture (biodiesel) was investigated in this study from linseed oil, low-cost alternative feedstock, using an alkaline catalyst with green reagent. Abstract : The synthesis of monoacylglycerol (MAG) through the glycerolysis of ethyl ester mixture (biodiesel) was investigated in this study from linseed oil, low-cost alternative feedstock, using an alkaline catalyst with green reagent. The transesterification double step process (TDSP), reaction with ethanol to ethyl esters yielded 97%. In the glycerolysis reaction, the optimum operating condition was in a temperature of 130 °C with 5% sodium hydroxide (NaOH) in 1 : 5 biodiesel–glycerol and 12 h reaction time, in open reactor. The reaction conditions showed an interesting conversion and monoacylglycerol yield of 98% and 76%, respectively. The determination and characterization of reaction products was carried out by Gas Chromatography (GC) method, Infrared Spectroscopy (IR), Thermogravimetric Analysis (TGA) and Hydrogen Nuclear Magnetic Resonance Spectroscopy ( 1 H NMR).